Intellectual capital and quality of service at the Faculty of Business Sciences at the Private University of Tacna - Peñaloza Arana, Eloyna Lucia (2014)
Objective: The present research was conducted in order to determine the influence of intellectual capital in the quality of service in the Faculty of Business at the Private University of Tacna 2012. Method: The work corresponds, whose level corresponds to relational and non-experimental design , transactional , and that it was the period 2012. For this purpose we considered the information obtained through the application of the questionnaire measuring instrument for assessing the intellectual capital and the quality of service provided in FACEM, which were applied to teachers and students with technical survey, using the Likert scale. After the phase of analysis and interpretation of the results was determined that in the Faculty of Business Studies of the Private University of Tacna, intellectual capital significantly influences the quality of service, 2012. The measurement models 24 scale indicators for intellectual capital, and 9 to competitiveness, and it is found that the set of intellectual capital assets have a positive influence on competitiveness. Result: They have determined that the brainpower evaluated through its human, structural and relational capital size is adequate and the quality of service according to dimensions tangibles, reliability, responsiveness, assurance and empathy is perceived as fair by students and teachers the FACEM. Conclusions: Definite emphasize the enhancement of intellectual capital to provide better quality of service and thereby convert the FACEM in model school at the Private University of Tacna.